Controlling the chemical composition of garnet with hydroxy groups for humic acid removal. Issue 7 (1st April 2023) - Maeda, Hirotaka; Minowa, Shogo; Urushihara, Daisuke; Asaka, Toru
Abstract: The removal of humic substances from aqueous solutions is a pivotal component in protecting water from environmental and health hazards. In this study, we successfully prepared garnet containing hydroxy groups with excellent adsorption properties for humic acid. The effects of the chemical composition of garnet on the adsorption properties were investigated. Heat treatment controlled the chemical composition by the dehydration of garnet and formation of silica-rich amorphous phase around the surface owing to the partial collapse of garnet. Compared to the untreated garnet, the treated garnet exhibited approximately seven times the adsorption properties for humic acid. The enhanced adsorption properties were related to the dramatic increase in pH owing to the amorphous phase and surface exposure of garnet with adequate hydroxyl groups as adsorption sites after soaking the treated garnet in a solution with humic acid.